2022
DOI: 10.1108/jcm-03-2021-4545
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic racism in inter-culture service encounter

Abstract: Purpose Language plays an important role in a successful service exchange, but it can become a source of discrimination if one party is a non-native speaker in the host country. This study aims to examine the linguistic racism that non-native customers experience in Inter Culture Service Encounters (ICSEs) and delves into factors that contribute to the underlying psychological responses and the behavioral outcomes. Design/methodology/approach A phenomenological approach was used where 16 individuals were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 93 publications
(136 reference statements)
1
7
0
Order By: Relevance
“…To escape, people may also turn to close others (Thapa et al , 2022). Research indicates that seeking social support helps individuals more effectively with long-term health benefits and psychological well-being (Gurung et al , 1997; Malik and Paswan, 2022; Pierce et al , 1996). Escapism or the self-selected detachment from one's immediate world through the consumption of social media resources (Dolan et al , 2016; Eisenbeiss et al , 2012; Whiting and Williams, 2013) such as text messaging (Grellhesl and Punyanunt-Carter, 2012), gaming (Billieux et al , 2015; Kuss and Griffiths, 2012), storytelling (Lund et al , 2018), gambling (Griffiths et al , 2010) and celebrity following (Maltby et al , 2001; McCutcheon et al , 2002; Reeves et al , 2012) has long been a popular topic in consumer research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To escape, people may also turn to close others (Thapa et al , 2022). Research indicates that seeking social support helps individuals more effectively with long-term health benefits and psychological well-being (Gurung et al , 1997; Malik and Paswan, 2022; Pierce et al , 1996). Escapism or the self-selected detachment from one's immediate world through the consumption of social media resources (Dolan et al , 2016; Eisenbeiss et al , 2012; Whiting and Williams, 2013) such as text messaging (Grellhesl and Punyanunt-Carter, 2012), gaming (Billieux et al , 2015; Kuss and Griffiths, 2012), storytelling (Lund et al , 2018), gambling (Griffiths et al , 2010) and celebrity following (Maltby et al , 2001; McCutcheon et al , 2002; Reeves et al , 2012) has long been a popular topic in consumer research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The negative psychological responses experience by nonnative customers would encourage them to avoid direct interaction with the service provider and, if possible, choose technology-mediated channels, i.e. smart services (Malik and Paswan, 2022). There is evidence that individuals who attribute communication difficulties to the stereotypes attached to their language varieties are more likely to avoid direct conversations in the future (Derwing, 2003).…”
Section: Interaction Comfortmentioning
confidence: 99%
“…One dimension that reflects such an assessment is one’s sense of social integration, which is based on the evaluation of the quality of their relationships, depicting the extent of commonness, and the feeling of belonging to the society (Feng et al , 2019; Keyes, 1998). Moreover, sociolinguistic literature also indicates that vulnerability among non-native speakers may arise due to the stigma attached to their limited language proficiency, eventually affecting their well-being (Jang and Kim, 2019; Jayasundara et al , 2020; Malik and Paswan, 2022). These studies have identified two psychological outcomes of the perceived stigma attached to their language variation – intergroup anxiety (Osborne, 2001; Stephan, 2014) and lack of social belongingness (Chaffee et al , 2020; Gluszek and Dovidio, 2010a, 2010b; Richman and Leary, 2009; Walton and Cohen, 2007).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations